2020
DOI: 10.3390/rs12172697
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Sea Surface Temperature in the China Seas Based on Long Short-Term Memory Neural Networks

Abstract: Sea surface temperature (SST) in the China Seas has shown an enhanced response in the accelerated global warming period and the hiatus period, causing local climate changes and affecting the health of coastal marine ecological systems. Therefore, SST distribution prediction in this area, especially seasonal and yearly predictions, could provide information to help understand and assess the future consequences of SST changes. The past few years have witnessed the applications and achievements of neural network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 38 publications
(42 reference statements)
0
21
0
Order By: Relevance
“…Generally speaking, the error increased with the increase of model prediction time. Lei G. [9] found that the accuracy of prediction one month in advance was the highest, with an error of 0.5 °C; When predicting 2 months in advance, RMSE increased to 0.59 °C; When predicting 12 months in advance, RMSE reached a peak of about 0.66 °C. So, it is obvious that with the increase of lead time, RMSE increases slowly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally speaking, the error increased with the increase of model prediction time. Lei G. [9] found that the accuracy of prediction one month in advance was the highest, with an error of 0.5 °C; When predicting 2 months in advance, RMSE increased to 0.59 °C; When predicting 12 months in advance, RMSE reached a peak of about 0.66 °C. So, it is obvious that with the increase of lead time, RMSE increases slowly.…”
Section: Discussionmentioning
confidence: 99%
“…Xiao et al (2019) [8] established an LSTM model in the East China Sea using 36 years of spaceborne sea surface temperature data; the model is accurate for the daily prediction of the short-term and medium-term sea surface temperature field. L. Guan et al (2020) [9] divided the entire China Sea and its adjacent area into 130 small regions using the self-organizing map algorithm, constructed an LSTM model for each region to predict its SST, and found that the root-mean-square error (RMSE) of the forecasts at 1 month in advance was 0.5 • C. In summary, previous studies have mostly used data sets to make short-term predictions of regional SST, in which the selected feature is rather simple. The prediction of sea temperature over large areas of water and a long period has been rarely investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [ 37 ], the authors proposed building a predictive model for predicting the SST of the entire China Sea. They utilized collected data over 12 months.…”
Section: Related Workmentioning
confidence: 99%
“…The proposed scheme is able to outperform other conventional benchmarks with a reduced input sequence length. The authors in [99] adopt an LSTM for predicting sea surface temperature over the China Seas for 12-month lead time. Considering the sub-regional feature differences within the study area, they use self-organizing feature maps to classify the data first, and then use the classification results as additional inputs for the DL network.…”
Section: Sea Surface Temperaturementioning
confidence: 99%